Atypical Fragility Fractures due to Bony or Soft Tissue Phosphaturic Mesenchymal Tumors: A Report of Two Cases - Stephanie M. Clegg; Emily S. Eiel; Sara Fine; Rachel I. Gafni; Mathew J. Most (Case Reports in Orthopedics)
Introduction. Tumor-induced osteomalacia (TIO) is a rare paraneoplastic disorder where patients present with hypophosphatemia, chronic diffuse bone pain, and occasionally fractures. Benign phosphaturic mesenchymal tumors (PMT) are responsible for the TIO and are largely soft tissue tumors. Cases. Two male patients with TIO secondary to PMT were reported—one in the bony scapula and the other in the plantar foot soft tissue. The first case describes a 63-year-old Caucasian male, who sustained an intertrochanteric proximal femur stress fracture and approximately two years of diffuse bone pain and hypophosphatemia. Wide excision of a left scapula boney lesion resulted in immediate resolution of his electrolyte abnormalities and bone pain. Case 2 describes a 58-year-old male with four years of multifocal bone pain and atraumatic fractures. A 68Ga-DOTATATE-positron emission tomography/computed tomography (PET/CT) scan identified a soft tissue tumor in his plantar foot, which was ultimately excised. He also experienced near immediate resolution of his pain and no additional fractures. Conclusion. TIO is a rare condition presenting with chronic multifocal bone pain, stress fractures, and hypophosphatemia. These two cases highlight that the causative tumor may originate in soft tissue or bone. Furthermore, a high index of suspicion, along with fibroblast growth factor-23 testing and DOTATATE-PET/CT localization, can help with diagnosis and minimize treatment delays.